Perancangan Aplikasi E-Commerce Pada Raisa Store Menggunakan Single Page Application (SPA) Teknologi Berbasis Web Dengan Metode Extreme Programming - Muhamad Iqbal Halim; Aries Saifudin (CV. Multi Kreasi Media, 2023)
E-commerce or can be called electronic commerce is the buying, selling, marketing, and services via the internet or computer networks. The rapid development of the internet is a driving factor for the development of e-commerce. The Internet is a global network that can access all computers in the world. The use this time is the extreme programming method, which is a suitable method for e-commerce applications because it is based on the planning stage that requires an understanding of the application, then at the design stage of the system design, the coding stage is the writing process, and the testing stage. The system or application that has been created is tested by trying all the features in the application to make sure that there are no features that have errors. Success in running an e-commerce business greatly affects consumer factors. From the observations that have been made, as well as the results of data processing, it can be found that there are several internet trust users, both of which influence the success of running e-commerce. The test results contained in the BlackBox can produce a conclusion that the e-commerce application gets very satisfactory results in testing features and functionality.